According to the question, Present ages of (X + Y) = 45 × 2 = 90…. (1) Than, the Present ages of (X + Z) = 32 × 2 = 64…. (2) Than, the Present ages of (Y + Z) = 12 × 2 = 18….. (3) Therefore From equations (1), (2) and (3), we get Present ages of (X + Y + Z) = (90 + 64 + 18)/2 = 86 years Therefore From equation (3)we will get the, present age of ‘X’ = 86 – 18 = 68 years
Fill in the blank with the most appropriate word.
Select the most appropriate option for blank no. 1.
Select the most appropriate option for blank No. 5.
Fill in the blank with the most appropriate word.
Find the appropriate word.
 Select the most appropriate option to fill in blank
Find the appropriate word.
Find the appropriate word.
Find the appropriate word.
 Select the most appropriate option to fill in blank number 1.